Implementasi Jelajah Si Ocica Dalam Pembelajaran Ilmu Pengetahuan Alam dan Sosial di Sekolah Dasar Negeri Kaliwungu - Tri Kusmiyati (Program Studi Pendidikan Guru Madrasah Ibtidaiyyah (PGMI) IAINU Kebeumen, 2026)
Low motivation and inappropriate teaching strategies on the part of teachers are the main obstacles to creating an active and contextual learning process. This study aims to improve student motivation and learning outcomes through the Jelajah Si OCICA strategy in Deep Learning. The research method used was a qualitative descriptive approach based on best practices, conducted in the third-grade class at Kaliwungu Public Elementary School with 17 students as research subjects. Data were collected through observation, questionnaires, and students’ academic records. The results indicate that the implementation of the “Jelajah Si OCICA” strategy had a significant impact on improving the quality of learning. Students became more active, enthusiastic, and confident in expressing and communicating the results of their observations of the environment outside the classroom. This increase in motivation was directly correlated with academic achievement, as 94% of students successfully met the passing grade threshold. The conclusion of this study is that the “Jelajah Si OCICA” strategy in Deep Learning has proven effective in enhancing student motivation and learning outcomes. This innovative strategy is recommended for adoption and dissemination in a broader educational context to create a safe, comfortable, and enjoyable learning environment.